Keys to Achieving Target First Medical Contact to Balloon Times and Bypassing Emergency Department More Important Than Distance - Saad Ezad; Allan J. Davies; Hooria Cheema; Trent Williams; James Leitch (Cardiology Research and Practice)
Background. Australian guidelines advocate primary percutaneous coronary intervention (PPCI) as the reperfusion strategy of choice for ST elevation myocardial infarction (STEMI) in patients in whom it can be performed within 90 minutes of first medical contact; otherwise, fibrinolytic therapy is preferred. In a large health district, the reperfusion strategy is often chosen in the prehospital setting. We sought to identify a distance from a PCI centre, which made it unlikely first medical contact to balloon time (FMCTB) of less than 90 minutes could be achieved in the Hunter New England health district and to identify causes of delay in patients who were triaged to a PPCI strategy. Methods and Results. We studied 116 patients presenting via the ambulance service with STEMI from January 2016 to December 2016. In patients who were taken directly to the cardiac catheterisation lab, a maximum distance of 50 km from hospital resulted in 75% of patients receiving PCI within 90 minutes and approximately 95% of patients receiving PCI within 120 minutes. Patients who bypassed the emergency department (ED) were significantly more likely to have FMCTB of less than 90 minutes (p<0.001) despite having a longer travel distance (28.5 km versus 17.4 km, p<0.001). Patients transiting via the ED were significantly more likely to present out of hours (60 versus 24.2% p<0.001). Conclusions. Patients who do not bypass the ED have a longer FMCTB across all spectrum of distances from the PCI centre; therefore, bypassing the ED is key to achieving target FMCTB times. Using a cutoff distance of 50 km may reduce human error in estimating travel time to our PCI centre and thereby identifying patients who should receive prehospital thrombolysis.